Legal Analysis of The Criminal Responsibility of Children in The Criminal Act of Insulting Children to Commit Sexual Interculation (Study of Decision Number 1/Pid.Sus.Anak/2025/Pn Bjm) - Akbar, Robby; Gunarto, Gunarto (Jurnal Hukum Khaira Ummah, 2025)
This research aims to analyze the criminal responsibility of children in the crime of inducing a child to engage in sexual intercourse, using the case study of Decision Number 1/Pid.Sus.Anak/2025/PN Bjm. The research focus includes the application of criminal liability principles to children, the legal factors influencing children's criminal liability, special legal treatment and protection, as well as efforts to reform laws and policies on children's criminal law enforcement to make it more effective in the future. The research method uses a juridical-normative approach, with analysis of court decision documents, relevant legislation, and legal literature. The research results indicate that the application of the principles of criminal responsibility for children prioritizes guidance and rehabilitation, not solely retributive punishment. Legal factors such as the age of criminal responsibility, the ability to be held accountable, the element of fault, and the causal relationship are the main considerations in determining a child's accountability. Additionally, diversion mechanisms, legal protection, and psychological support are important instruments for ensuring children's rights are protected. This research also highlights the need for legal and policy updates, including improving diversion mechanisms, integrating restorative justice principles, using information technology for monitoring rehabilitation programs, and adopting best practices from other countries that are effective in reducing child recidivism. In conclusion, the application of the principles of juvenile criminal responsibility in Indonesia has already integrated theories of criminal responsibility, rehabilitation, and restorative justice, but legal and policy reforms are still needed to improve effectiveness, fairness, and protection for both child offenders and victims.